Reconstructing the Pre-Meroitic Indigenous Pantheon of Kush - Almansa-Villatoro, M. Victoria (Journal of ancient Near Eastern religions, 2018)
This article sets out to address questions concerning local religious traditions in ancient Nubia. Data concerning Egyptian gods in the Sudan are introduced, then the existence of unattested local pre-Meroitic gods is reconstructed using mainly external literary sources and an analysis of divine names. A review of other archaeological evidence from an iconographic point of view is also attempted, concluding with the presentation of Meroitic gods and their relation with earlier traditions. This study proposes that Egyptian religious beliefs were well integrated in both official and popular cults in Nubia. The Egyptian and the Sudanese cultures were constantly in contact in the border area and this nexus eased the transmission of traditions and iconographical elements in a bidirectional way. The Meroitic gods are directly reminiscent of the reconstructed indigenous Kushite pantheon in many aspects, and this fact attests to an attempt by the Meroitic rulers to recover their Nubian cultural identity.